Waqf effectiveness in Nigeria: problems and solutions - Fa-Yusuf, Habeebah Simisola; Busari, Saheed Abdullahi; Lawal Shuaibu, Bilkis (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia, 2021)
The efficiency of the institution of Waqf in alleviating poverty is undisputable and Nigeria as a country with a significant Muslim population stands to benefit immensely from well-functioning Waqf institutions. Despite the presence of Waqf in Nigeria, the country still experiences increasing levels of poverty. This study aims to find the problems hindering the effectiveness of the Waqf operation in alleviating poverty in Nigeria. It uses the thematic framework medium of interviewing as a methodology of retrieving the necessary data. From the analysis, it was evident that a combination of a lack of awareness, lack of transparency as well as corrupt practices is what has led to the inefficiency of Waqf operations in Nigeria. The study concludes by discussing solutions that can be employed to remedy the challenges, including producing experts in Waqf management, providing tax exemptions for Waqf donors, enacting Federal laws relating to Awqaf and awareness creation.